Prediction of expiratory desflurane and sevoflurane concentrations in lung-healthy patients utilizing cardiac output and alveolar ventilation matched pharmacokinetic models: A comparative observational study - Weber, Jonas (Medicine (Baltimore), 2021)
The Gas Man simulation software provides an opportunity to teach, understand and examine the pharmacokinetics of volatile anesthetics. The primary aim of this study was to investigate the accuracy of a cardiac output and alveolar ventilation matched Gas Man model and to compare its predictive performance with the standard pharmacokinetic model using patient data. Therefore, patient data from volatile anesthesia were successively compared to simulated administration of desflurane and sevoflurane for the standard and a parameter-matched simulation model with modified alveolar ventilation and cardiac output. We calculated the root-mean-square deviation (RMSD) between measured and calculated induction, maintenance and elimination and the expiratory decrement times during emergence and recovery for the standard and the parameter-matched model. During induction, RMSDs for the standard Gas Man simulation model were higher than for the parameter-matched Gas Man simulation model [induction (desflurane), standard: 1.8 (0.4) % Atm, parameter-matched: 0.9 (0.5) % Atm., P = .001; induction (sevoflurane), standard: 1.2 (0.9) % Atm, parameter-matched: 0.4 (0.4) % Atm, P = .029]. During elimination, RMSDs for the standard Gas Man simulation model were higher than for the parameter-matched Gas Man simulation model [elimination (desflurane), standard: 0.7 (0.6) % Atm, parameter-matched: 0.2 (0.2) % Atm, P = .001; elimination (sevoflurane), standard: 0.7 (0.5) % Atm, parameter-matched: 0.2 (0.2) % Atm, P = .008]. The RMSDs during the maintenance of anesthesia and the expiratory decrement times during emergence and recovery showed no significant differences between the patient and simulated data for both simulation models. Gas Man simulation software predicts expiratory concentrations of desflurane and sevoflurane in humans with good accuracy, especially when compared to models for intravenous anesthetics. Enhancing the standard model by ventilation and hemodynamic input variables increases the predictive performance of the simulation model. In most patients and clinical scenarios, the predictive performance of the standard Gas Man simulation model will be high enough to estimate pharmacokinetics of desflurane and sevoflurane with appropriate accuracy.